PROSPEK EKONOMI DAERAH SUMATERA SELATAN - Bernadette Robiani (Jurnal Ekonomi Pembangunan, 2006)
The prospect of economy of  an economy depends on its economic performance for many years. This paper describes the economy prospect of South Sumatera Province based on macroeconomic condition; growth, sectoral contribution, population and employment. Specifically, it also describes the industrial sector and balance trade. It is found that South Sumatera's growth showed an increasing pattern during the period analysis eventhough it less than national growth. The contribution to GDRB is dominated by three sectors; agriculture, industry and trade. Each of them contributes as much as 27%, 18% and 17.5%. Based on the GDRB expenditure, the highest expenditure comes from household consumption as much as 58%. Based on the ratio of  Industrial sector and agricultural GDRB, it is found that the role of industrial sector is dominant. The sectoral prospect of South Sumatera is in agriculture sector especially  crops and plantation and in industrial sector especially in food industry. The effort that can be done  to optimize the sectoral role are increase the productivity, create the sectoral linkage and innovate product diversification and differentiation. Keywords: Growth, Sectoral Contribution, Labour Absorption, Export and Import